Implementing genuine participatory action research with Aboriginal Elders: The Ngulluk Koolunga Ngulluk Koort project. Issue 2 (June 2022) - Scrine, Clair; Farrant, Brad; Michie, Carol; Shepherd, Carrington; Wright, Michael
This paper describes the processes involved in establishing a genuinely collaborative and participatory role for nine Aboriginal Elders in a five-year participatory action research project focused on early child development in the Perth metropolitan area of Western Australia. The project goals are to better inform and align policy and program design with Aboriginal values, world views and concepts of childhood. The Elder's authority in the design, conduct and outputs of the research are intended to adhere to a decolonising approach, whereby Aboriginal people have power and voice in ways that are aligned to their values and beliefs. Requirements for research that is collaborative, relational, participatory and reflexive are not straightforward or easily achieved, and the process of working with the nine Elders in their roles as Co-researchers has not been without its challenges. This paper explores the challenges and opportunities of working with Aboriginal Elders as Co-researchers and seeks to enhance understanding of the necessity of incorporating an Aboriginal worldview and knowledge framework in this way.